PRODUKSI PEKTIN DARI KULIT JERUK NIPIS (Citrus aurantifolis S) DENGAN INTERAKSI SUHU DAN LAMA EKSTRAKSI - Yoakhim Y. E. Oessoe (AGRI-SOSIOEKONOMI, 2021)
Lime rind is agricultural waste. Its existence is easy to find, especially in restaurants or food stalls. Lime rind still has the potential to be processed, including the extraction process to obtain pectin. This study aims to determine the right temperature and extraction time in order to obtain the best yield and quality of pectin from lime rind. This research was held in the laboratory of the Faculty of Agriculture, Department of Agricultural Technology, especially the laboratory for processing food products and the laboratory of the Manado Industrial Research and Standardization Center. This research is a laboratory research using a Completely Randomized Design (CRD) method with two factors, those are the extraction temperature of 60 ° C, 80 ° C, and 100 ° C and the extraction time of 30, 60 and 90 minutes with three replications. The observations made were pectin yield, methoxyl content, moisture content and ash content. The results showed that the temperature of 80 ° C and the extraction time of 60 minutes produced the best pectin with a methoxyl content of more than 7%, a moisture content of 9.73-13.77% and an ash content below 10%.